Consecuencias del covid-19 en la inversión extranjera directa en Colombia (2021)
The world is currently suffering the aftermath of a pandemic that generated deaths, poverty, disease and a global economic contraction of 4.3%, caused by the rapid spread of the covid-19 virus (coronavirus) and a series of countermeasures to ensure the global health. Well, each country, following the recommendations of the highest health speaker "the World Health Organization-WHO", and under the autonomy to govern and ensure security within the national territory, measures are developed to stop the spread of the virus. This work aims to show the effects that the emergence of the covid-19 virus generated on foreign direct investment in the periods 2020 - 2021-2 in Colombia. A compilation and analysis of information regarding the economy and factors that affect it in Latin America and Colombia is developed to contextualize the general economic situation. Subsequently, figures of foreign direct investment were collected from databases, news and the bank of the republic to analyze and demonstrate the effect of the outbreak of the coronavirus in Colombia.